Anticholinesterase and antioxidant potentials of Nonea micrantha Bioss. & Reut along with GC-MS analysis. Issue 1 (December 2017) - Imran, Muhammad; Ullah, Farhat; Ayaz, Muhammad; Sadiq, Abdul; Shah, Muhammad; Jan, Muhammad; Ullah, Farman
Abstract Background Nonea micrantha Boiss. & Reut . being an unexplored member of Boraginaceae was investigated for GC/MS analysis, acetylcholinesterase (AChE), butyrylcholinesterase (BChE) inhibitory and antioxidant activities in an attempt to find its effectiveness in neurological disorders. Methods The AChE and BChE inhibitory activities of crude methanolic extract (Nm.Cr), subsequent fractions;n -hexane (Nm.Hex), chloroform (Nm.Cf), ethyl acetate (Nm.EtAc), aqueous (Nm.Aq) and crude saponins (Nm.Sp) fromN. micrantha were conducted using Ellman's assay. The antioxidant activity of the plant samples using DPPH and ABTS free radical scavenging potential following quantitative spectrophotometric and qualitative TLC method were also studied. Moreover the total reducing power (TRP) of all the samples was also figured out. Results The GC/Ms analysis confirmed that the plant is rich in bioactive molecules. Among different fractions, Nm.Hex, Nm.EtAc and Nm.Cf exhibited highest AChE inhibitory activities causing 75.51 ± 0.73, 68.54 ± 0.59 and 63.48 ± 0.59% enzyme inhibition respectively and IC50 of 44, 100 and 144 μg/mL respectively. In BChE inhibiton assay, Nm.Aq, Nm.Sp and Nm.Cr showed highest activity causing 83.49 ± 0.27, 81.49 ± 0.89 and 75.31 ± 0.56% enzyme inhibition with IC50 of 90, 110 and 44 μg/mL respectively. In DPPH assay, Nm.Aq, Nm.Cf, Nm.Hex and Nm.Cr were most potent exhibiting IC50 values of 3, 5, 93 and 120 μg/ml respectively. In ABTS assay Nm.EtAc, Nm.Aq, Nm.Sp and Nm.Cr showed IC50 values of 60, 95, 100 and 150 μg/mL respectively. Likewise ABTS inhibition was most prominent for Nm.Sp, Nm.EtAc and Nm.Aq causing 78.26 ± 0.49, 67.67 ± 0.73 and 63.58 ± 0.45% inhibition respectively at 1 mg/mL. These results were further confirmed by qualitative screening using DPPH and ABTS staining. Conclusions Our anticholinesterase and antioxidant results signify theN. micrantha as a potential source of natural bioactive compounds. Moreover isolation of natural bioactive compounds from this plant may lead to novel drug candidates against neurodegenerative disorders.